2015
DOI: 10.7439/ijbr.v6i5.1994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hematological parameters in primary hypertensives and normotensives of Sangareddy

Abstract: Background: Hypertension is the major health problem throughout the world because of its high prevalence and its association with increased risk of cardiovascular diseases. Aim: The aim of present study was to evaluate the hematological changes in primary hypertension in Sangareddy, Andhra Pradesh. Materials and Methods:In the present study, a total of 100 patients diagnosed for primary hypertension and 100 normotensive subjects were included. All the participants after taking informed consent were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 14 publications
11
12
1
1
Order By: Relevance
“…In our study, there was no significant difference in mean corpuscular hemoglobin concentration (MCHC) between HTN and NTN groups. These results are in contrast to those studies reported an increased or decreased level of MCHC in HTN subjects . The reason of this inconsistency may be related to the differences in population size and ethnicity.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…In our study, there was no significant difference in mean corpuscular hemoglobin concentration (MCHC) between HTN and NTN groups. These results are in contrast to those studies reported an increased or decreased level of MCHC in HTN subjects . The reason of this inconsistency may be related to the differences in population size and ethnicity.…”
Section: Discussioncontrasting
confidence: 98%
“…Babu et al. in a case–control study containing 100 hypertensive patients and 100 normotensive subjects demonstrated that MCV appears to be inversely related to systolic and diastolic blood pressure . Consistent with these findings, we showed that compared to the control group MCV is decreased in HTN individuals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations